TRANSFORMATION OF A NOVEL MURDER ON THE ORIENT EXPRESS INTO ITS FILM ADAPTATION USING ECRANIZATION STUDY - Aspriyanto, Yogy; Hastuti, Erni (Jurnal Pendidikan Bahasa dan Sastra, 2019)
The objectives of this research are to determine and analyze the ecranization process on the characters in novels and its film adaptation. This research used descriptive qualitative method. The importance of this research can give contribution for other researchers who want to conduct the research about ecranization processes such as addition, reduction and variation of change in terms of plot, character and setting. The research results in the ecranization process on the character occurs reduction, addition and variation of change. The reduction in both novels and films occurs because the duration of the film cannot be long, unlike in a novel with a long duration the film reduced characters, although undergo the reduction but does not omit or change the main of the story. The addition both novels and the film added characters to the film because the director wanted to give a creative impression on some scenes in the film and not monotonous as in the novel. The variation of change both novels and films occurred by the characters that were replaced because the director wanted to make a difference between the novel and the film and also variation of change in the character did not change the main storyline of the novel and the film.